Probing the Stability of Fluorescent Proteins by Terahertz Spectroscopy - Xu, M. Y.; George, D. K.; Jimenez, R.; Markelz, A. G. (2014 39th International Conference on Infrared, Millimeter, and Terahertz Waves, 2014)
The higher transmission through tissues of long wavelength light motivates the development of fluorescent proteins with excitation shifted to the red. However red fluorescent proteins (RFPs) are more susceptible to photobleaching than their shorter wavelength counterparts. In particular RFPs are more susceptible to photobleaching [1]. A possible reason for this is a decrease in the structural stability of the beta barrel. Measurements of structural stability include atomic root mean squared displacement <x(2)> measured by the X-ray B-factor and neutron quasi elastic scattering. To date, X-ray measurements of RFP's do not indicate a structural stability change and systematic scattering studies have not been performed. Using THz dielectric response we examine if the picosecond structural flexibility decreases with increasing FP stability.
Keywords: dynamics